Quick-drying corrosion-resistant finish paint and preparation process thereof

By preparing quick-drying corrosion-resistant topcoat, using the combination of component A and component B, the rapid curing of topcoat and the improvement of wear resistance and corrosion resistance are achieved, solving the problems of long curing time and poor performance of ordinary topcoats, extending service life and expanding application fields.

CN119592176AActive Publication Date: 2025-03-11JIANGSU ANTEKE NEW MATERIALS RES INST CO LTD
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202411867257.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-03-11
Estimated Expiration
2044-12-18

AI Technical Summary

Technical Problem

Ordinary topcoat has a long curing time and is prone to sagging, resulting in uneven film thickness, poor corrosion and wear resistance, and short service life.

Method used

It adopts a quick-drying corrosion-resistant topcoat, consisting of component A and component B. Component A includes epoxy acrylate resin, anti-corrosion resin, thiolated stone calendering, etc. Component B includes photoinitiator and deionized water. It cures through photoinitiation to quickly form a tight mesh structure to enhance corrosion and wear resistance.

Benefits of technology

It realizes rapid curing of topcoat, avoids sagging, enhances wear and corrosion resistance, extends service life, and expands the application field of topcoat in corrosive media.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119592176A_ABST
    Figure CN119592176A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of finish paint, and discloses quick-drying corrosion-resistant finish paint and a preparation process thereof, the quick-drying corrosion-resistant finish paint is composed of a component A and a component B, wherein the component A is prepared from the following raw materials: epoxy acrylate resin, anti-corrosion resin, sulfhydrylated dickite, a defoaming agent, an antioxidant, an emulsifying agent and a flatting agent; the component B comprises the following raw materials: a photoinitiator and deionized water; wherein the anti-corrosion resin is prepared by reacting modified vinyl chloride-vinyl acetate resin with 2-amino-5-fluorobenzotrifluoride; the modified vinyl chloride-vinyl acetate resin is prepared by reacting hydroxyl vinyl chloride-vinyl acetate resin with 2-chloroacrylic acid; the sulfhydrylated dickite is prepared by reacting the modified dickite with mercaptoethylamine; the modified dickite is prepared by intercalating (3-carboxypropyl) trimethyl ammonium chloride into dickite. The finish paint prepared by the invention has excellent quick-drying property, wear resistance and corrosion resistance, and the application field of the finish paint is greatly expanded.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of topcoats, and in particular to a quick-drying corrosion-resistant topcoat and a preparation process thereof. Background Art

[0002] Topcoat is a kind of coating that acts on the surface of objects to play a decorative and protective role. It is diverse and functional and is widely used in many fields. Nowadays, with the development of science and technology and the progress of industry, people have higher and higher requirements for the aesthetics and functionality of the surface of objects, and the limitations of traditional ordinary topcoats are gradually emerging.

[0003] The curing speed of topcoat has always been a key factor restricting its wide application. After ordinary topcoat is applied, it takes a long time for cross-linking reaction to reach the ideal curing state and form a solid paint film. If the curing time is too long, the paint will easily flow along the surface of the coated object under the action of gravity, forming a sagging phenomenon, which will not only destroy the aesthetics of the coating and cause its surface to be uneven, but also cause uneven coating thickness, resulting in thin coatings in some areas that are easily eroded, and thick coatings in some areas, which are prone to internal stress and increase the risk of cracking. Therefore, ordinary topcoats are difficult to use on objects with uneven surfaces. At the same time, ordinary topcoats are often subjected to physical friction when used on the surface of objects. Their wear resistance is general and they are easily damaged under long-term friction. They need to be remedied or replaced frequently. When used in corrosive media, ordinary topcoats have poor corrosion resistance. The coating on the surface of the object will discolor, bubble, or even fall off due to the action of the corrosive medium, which not only seriously affects the aesthetics of the object, but also loses its protective effect on the object.

[0004] The patent with publication number CN106280867B discloses a high temperature resistant and anti-corrosion epoxy paint and a preparation method thereof. The prepared epoxy paint has excellent corrosion resistance, rust resistance, salt and alkali resistance, high temperature resistance, high hardness, wear resistance, pressure resistance, and is not easy to break brittlely, and has excellent stability and crack resistance. Although the epoxy paint prepared by this patent has a variety of excellent properties and can meet the use requirements in a variety of environments, the curing efficiency is not improved. When used on irregular surfaces, it is easy to sag, thereby affecting the service life of the paint film. Summary of the invention

[0005] The purpose of the present invention is to provide a quick-drying corrosion-resistant topcoat and a preparation process thereof, which solves the following technical problems: (1) the curing time of ordinary topcoats is short and they are easy to sag after coating, resulting in uneven film thickness; (2) the corrosion resistance and wear resistance of ordinary topcoats are average and their service life is short.

[0006] The purpose of the present invention can be achieved through the following technical solutions: A quick-drying corrosion-resistant topcoat consists of component A and component B; the component A comprises the following raw materials in parts by weight: 60-80 parts of epoxy acrylate resin, 25-30 parts of anti-corrosion resin, 12-15 parts of mercaptolated dickite, 2-3 parts of defoamer, 3-5 parts of antioxidant, 2-5 parts of emulsifier, and 1-3 parts of leveling agent; the component B comprises the following raw materials in parts by weight: 3-6 parts of photoinitiator, and 120-150 parts of deionized water; the anti-corrosion resin is prepared by reacting modified chloroacetic acid resin with 2-amino-5-fluorotrifluorotoluene; the modified chloroacetic acid resin is prepared by reacting hydroxychloroacetic acid resin with 2-chloroacrylic acid; the mercaptolated dickite is prepared by reacting modified dickite with mercaptoethylamine; the modified dickite is prepared by (3-carboxypropyl)trimethylammonium chloride intercalated dickite.

[0007] Furthermore, the defoaming agent is any one of dimethyl silicone oil and fatty alcohol polyoxyethylene ether; the antioxidant is any one of antioxidant 1010, antioxidant 2246, and antioxidant 1135; the emulsifier is any one of calcium dodecylbenzene sulfonate, sodium dodecyl polyoxyethylene ether sulfate, alkylphenol polyoxyethylene ether sulfonate, sodium dodecylbenzene sulfonate, and sodium dodecyl sulfate; the leveling agent is any one of polybutyl acrylate and polyethyl acrylate; the photoinitiator is any one of benzoin dimethyl ether, thioxanthone, benzophenone, and 1-(4-isopropylphenyl)-2-hydroxy-2-methylpropane-1-one.

[0008] Furthermore, the preparation method of the anti-corrosion resin comprises the following steps: S1: placing hydroxychloroacetic acid resin and 2-chloroacrylic acid in toluene, stirring and mixing, adding p-toluenesulfonic acid, heating to react, and collecting the product after reduced pressure distillation to obtain a modified chloroacetic acid resin; S2: Place the modified chloroacetic acid resin and 2-amino-5-fluorotrifluorotoluene in N,N-dimethylformamide, add a catalyst, heat to 55-65°C and react for 6-8h, collect the product after reduced pressure distillation, and obtain an anti-corrosion resin.

[0009] In this scheme, the hydroxyl group in the structure of the hydroxychlorovinyl resin and the carboxyl group in the structure of 2-chloroacrylic acid undergo an esterification reaction under the action of p-toluenesulfonic acid, and a double bond is introduced into the polymer chain segment of the chlorovinyl resin to obtain a modified chlorovinyl resin. Then, under the action of a catalyst, the active chlorine in the structure of the modified chlorovinyl resin undergoes a substitution reaction with the amino group in the structure of 2-amino-5-fluorotrifluorotoluene in N,N-dimethylformamide to obtain an anti-corrosion resin. The anti-corrosion resin uses the hydroxychlorovinyl resin as a polymer matrix chain segment, and the multiple double bonds introduced in its structure can participate in the curing process of the topcoat. , so that it interacts with the topcoat matrix material, cross-links and entangles to form a tight network structure, thereby effectively enhancing the corrosion resistance and wear resistance of the topcoat. At the same time, organic fluorine is introduced into the anti-corrosion resin structure to make it contain a large number of CF bonds. These bonds have small polarization rate, short bond distance but large bond energy and excellent chemical stability, and can effectively resist the erosion of corrosive media, further enhancing the corrosion resistance of the topcoat, and enabling it to maintain its structural stability in corrosive media, effectively expanding the use field of the topcoat, and greatly increasing the service life of the topcoat in corrosive media.

[0010] Furthermore, in step S1, the temperature of the temperature-raising reaction is 90-95° C. and the time is 3-5 hours.

[0011] Furthermore, in step S2, the catalyst is potassium carbonate.

[0012] Furthermore, the preparation method of the mercaptolated dickite comprises the following steps: SS1: Place dickite in deionized water, ultrasonically disperse for 10-15 minutes, add (3-carboxypropyl)trimethylammonium chloride, stir thoroughly for 8-10 hours, filter, wash and dry to obtain modified dickite; SS2: Place the modified dickite in anhydrous ethanol, ultrasonically disperse it for 12-15 minutes, add mercaptoethylamine and a composite catalyst, heat to 60-65°C and react for 5-6 hours, filter, wash and dry to obtain the mercapto dickite.

[0013] In this scheme, (3-carboxypropyl)trimethylammonium chloride with a quaternary ammonium group is used to perform intercalation modification on dickite to obtain modified dickite containing a carboxyl group. Then, under the action of a composite catalyst, the carboxyl group in the modified dickite structure reacts with the amino group in the mercaptoethylamine structure to obtain thiolated dickite. This thiolated dickite has good compatibility with the topcoat matrix material and can effectively enhance the wear resistance of the topcoat. At the same time, its structure has multiple thiols. During the UV curing process of the topcoat, the thiol-ene can undergo a click reaction, which can effectively reduce oxygen inhibition during the UV curing process and form a better cross-linking structure, thereby effectively accelerating the curing process of the topcoat and enabling it to cure quickly. When applied to the protection of convex surfaces or irregular surfaces, it can effectively avoid the problem of uneven paint film thickness caused by topcoat sagging and extend the service life of the paint film.

[0014] Furthermore, in step SS2, the composite catalyst is 4-dimethylaminopyridine and dicyclohexylcarbodiimide in a ratio of 0.3-1:0.9-3.

[0015] A preparation process of a quick-drying corrosion-resistant topcoat comprises the following steps: Step 1, epoxy acrylate resin, anti-corrosion resin, mercapto-modified dickite, defoamer, antioxidant, emulsifier and leveling agent are mixed uniformly to obtain component A; Step 2: Evenly mix the photoinitiator and deionized water to obtain component B.

[0016] Beneficial effects of the present invention: The present invention prepares an anti-corrosion resin and mercapto-modified pyrolyte in the preparation process of the topcoat, so that the prepared topcoat has excellent wear resistance and corrosion resistance, can meet the use requirements in various environments, and has a long service life. At the same time, the topcoat prepared by the present invention has quick-drying properties, can effectively solve the problem of uneven paint film caused by sagging when the topcoat is used on irregular surfaces, and greatly expands the application field of the topcoat.

[0017] Of course, any product implementing the present invention does not necessarily need to achieve all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.

[0019] Figure 1 The present invention is a process flow chart for preparing the quick-drying corrosion-resistant topcoat. DETAILED DESCRIPTION

[0020] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0021] The preparation methods of the anticorrosive resin and mercapto-modified dickite in the following examples and comparative examples of the present invention are as follows: 1. Preparation of anti-corrosion resin S1: 3 g of hydroxychloroacetic acid resin and 2.5 g of 2-chloroacrylic acid are placed in 50 ml of toluene, stirred and mixed thoroughly, 0.2 g of p-toluenesulfonic acid is added, the temperature is raised to 90° C. for reaction for 3 h, and the product is collected after reduced pressure distillation to obtain a modified chloroacetic acid resin; S2: 3.2 g of modified chloroacetic acid resin and 3 g of 2-amino-5-fluorotrifluorotoluene were placed in 80 ml of N,N-dimethylformamide, 0.1 g of potassium carbonate was added, the temperature was raised to 55°C for reaction for 6 h, and the product was collected after reduced pressure distillation to obtain an anti-corrosion resin.

[0022] The nitrogen element analysis of the modified chlorovinyl resin and the anti-corrosion resin using a Carlo Erba 1106 element analyzer showed that the modified chlorovinyl resin did not contain nitrogen, while the nitrogen content in the anti-corrosion resin was 6.1%, which was caused by the reaction of active chlorine in the structure of the modified chlorovinyl resin with the amino group in the structure of 2-amino-5-fluorotrifluorotoluene.

[0023] 2. Preparation of thiolated dickite SS1: 2.5 g of dickite was placed in 100 ml of deionized water, ultrasonically dispersed for 10 min, 2.8 g of (3-carboxypropyl)trimethylammonium chloride was added, and the mixture was stirred for 8 h. The modified dickite was obtained after filtration, washing and drying. SS2: Place 3 g of modified diatomite in 120 ml of anhydrous ethanol, ultrasonically disperse for 12 minutes, then add 3.5 g of mercaptoethylamine, 0.3 g of 4-dimethylaminopyridine and 0.9 g of dicyclohexylcarbodiimide, heat to 60°C and react for 5 hours. After filtering, washing and drying, thiolated diatomite is obtained.

[0024] Analysis of the nitrogen and sulfur contents in modified diopside and thiolated diopside showed that the nitrogen content in modified diopside was 3.3%, and no sulfur was contained; the nitrogen content in thiolated diopside was 5.6%, and the sulfur content was 7.1%. Compared with modified diopside, the nitrogen content in thiolated diopside was significantly increased and sulfur appeared, which was caused by the reaction between the carboxyl group in the modified diopside structure and the amino group in the mercaptoethylamine structure. Example

[0025] Preparation technology of quick-drying corrosion-resistant topcoat Step 1, 60 parts of epoxy acrylate resin, 25 parts of anti-corrosion resin, 12 parts of mercapto dickite, 2 parts of dimethyl silicone oil, 3 parts of antioxidant 1010, 2 parts of calcium dodecylbenzene sulfonate, and 1 part of polyethyl acrylate are mixed uniformly to obtain component A; Step 2: Mix 3 parts of benzoin dimethyl ether and 120 parts of deionized water to obtain component B. Example

[0026] Preparation technology of quick-drying corrosion-resistant topcoat Step 1, 70 parts of epoxy acrylate resin, 28 parts of anti-corrosion resin, 13 parts of mercapto dickite, 2.5 parts of fatty alcohol polyoxyethylene ether, 4 parts of antioxidant 2246, 3 parts of sodium dodecyl polyoxyethylene ether sulfate, and 2 parts of polybutyl acrylate are mixed uniformly to obtain component A; Step 2: Evenly mix 4 parts of 1-(4-isopropylphenyl)-2-hydroxy-2-methylpropane-1-one and 135 parts of deionized water to obtain component B. Example

[0027] Preparation technology of quick-drying corrosion-resistant topcoat Step 1, 80 parts of epoxy acrylate resin, 30 parts of anti-corrosion resin, 15 parts of mercapto dickite, 3 parts of dimethyl silicone oil, 5 parts of antioxidant 1135, 5 parts of sodium dodecylbenzene sulfonate, and 3 parts of polyethyl acrylate are mixed uniformly to obtain component A; Step 2: Mix 6 parts of benzophenone and 150 parts of deionized water to obtain component B.

[0028] Comparative Example 1 Preparation process of topcoat Step 1, 70 parts of epoxy acrylate resin, 13 parts of mercapto dickite, 2.5 parts of fatty alcohol polyoxyethylene ether, 4 parts of antioxidant 2246, 3 parts of sodium dodecyl polyoxyethylene ether sulfate, and 2 parts of polybutyl acrylate are mixed uniformly to obtain component A; Step 2: Evenly mix 4 parts of 1-(4-isopropylphenyl)-2-hydroxy-2-methylpropane-1-one and 135 parts of deionized water to obtain component B.

[0029] Comparative Example 2 Preparation process of topcoat Step 1, 70 parts of epoxy acrylate resin, 28 parts of anti-corrosion resin, 2.5 parts of fatty alcohol polyoxyethylene ether, 4 parts of antioxidant 2246, 3 parts of sodium dodecyl polyoxyethylene ether sulfate, and 2 parts of polybutyl acrylate are mixed uniformly to obtain component A; Step 2: Evenly mix 4 parts of 1-(4-isopropylphenyl)-2-hydroxy-2-methylpropane-1-one and 135 parts of deionized water to obtain component B.

[0030] Comparative Example 3 Preparation process of topcoat Step 1, 70 parts of epoxy acrylate resin, 28 parts of modified chloroacetic acid resin, 13 parts of mercapto dickite, 2.5 parts of fatty alcohol polyoxyethylene ether, 4 parts of antioxidant 2246, 3 parts of sodium dodecyl polyoxyethylene ether sulfate, and 2 parts of polybutyl acrylate are mixed uniformly to obtain component A; Step 2: Evenly mix 4 parts of 1-(4-isopropylphenyl)-2-hydroxy-2-methylpropane-1-one and 135 parts of deionized water to obtain component B.

[0031] Comparative Example 4 Preparation process of topcoat Step 1, 70 parts of epoxy acrylate resin, 28 parts of anti-corrosion resin, 13 parts of modified ground stone, 2.5 parts of fatty alcohol polyoxyethylene ether, 4 parts of antioxidant 2246, 3 parts of sodium dodecyl polyoxyethylene ether sulfate, and 2 parts of polybutyl acrylate are mixed uniformly to obtain component A; Step 2: Evenly mix 4 parts of 1-(4-isopropylphenyl)-2-hydroxy-2-methylpropane-1-one and 135 parts of deionized water to obtain component B.

[0032] Performance Testing The topcoats prepared in Example 1 to Example 3 and Comparative Example 1 to Comparative Example 3 were used as samples, and component A and component B were mixed and coated on a steel plate that met the specifications. The topcoats were irradiated under ultraviolet light with a wavelength of 395nm and an energy density of 600mW / cm2 until they were cured. The cotton ball blowing method was used to determine whether the curing was complete. The curing time when the cotton ball could be blown away and no cotton fibers were left on the film surface was recorded by a stopwatch. Each group was tested 3 times, and the results were averaged to determine the curing rate of the sample. The cured samples were subjected to a wear resistance test in accordance with the reference standard GB / T1768-2006 to determine the wear resistance of the samples. The cured samples were subjected to a salt spray test in accordance with the reference standard GB / T1771-2007 to determine the corrosion resistance of the samples. The specific test results are shown in the table below:

[0033] It can be seen from the above table that the samples prepared in Examples 1 to 3 all have excellent wear resistance and corrosion resistance, and at the same time, have a short curing time and quick-drying characteristics. In the sample prepared in Comparative Example 1, no anti-corrosion resin was added, and the anti-corrosion ability was poor. In the sample prepared in Comparative Example 2, no thiolated distillate was added, and the wear resistance was not as good as that of the embodiment and the sample curing time was long. In the sample prepared in Comparative Example 3, modified chloroacetic acid resin and thiolated distillate were directly added, and the corrosion resistance needed to be improved. In the sample prepared in Comparative Example 4, modified distillate and anti-corrosion resin were directly added, and the sample curing time was long and the curing rate was slow.

[0034] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0035] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the scope defined by the concept of the invention, they should all fall within the protection scope of the present invention.

Claims

1. A quick-drying corrosion-resistant topcoat, characterized in that: The invention is composed of component A and component B; the component A comprises the following raw materials in parts by weight: 60-80 parts of epoxy acrylate resin, 25-30 parts of anticorrosion resin, 12-15 parts of mercapto-dihydrobenzene, 2-3 parts of defoamer, 3-5 parts of antioxidant, 2-5 parts of emulsifier and 1-3 parts of leveling agent; the component B comprises the following raw materials in parts by weight: 3-6 parts of photoinitiator and 120-150 parts of deionized water; the anticorrosion resin is prepared by the reaction of modified chloroacetic acid resin and 2-amino-5-fluorotrifluorotoluene; the modified chloroacetic acid resin is prepared by the reaction of hydroxychloroacetic acid resin and 2-chloroacrylic acid; the mercapto-dihydrobenzene is prepared by the reaction of modified benzene and mercaptoethylamine; the modified benzene is prepared by (3-carboxypropyl)trimethylammonium chloride intercalated benzene.

2. A quick-drying corrosion-resistant topcoat according to claim 1, characterized in that: The defoaming agent is any one of dimethyl silicone oil and fatty alcohol polyoxyethylene ether; the antioxidant is any one of antioxidant 1010, antioxidant 2246, and antioxidant 1135; the emulsifier is any one of calcium dodecylbenzene sulfonate, sodium dodecyl polyoxyethylene ether sulfate, alkylphenol polyoxyethylene ether sulfonate, sodium dodecylbenzene sulfonate, and sodium dodecyl sulfate; the leveling agent is any one of polybutyl acrylate and polyethyl acrylate; the photoinitiator is any one of benzoin dimethyl ether, thioxanthone, benzophenone, and 1-(4-isopropylphenyl)-2-hydroxy-2-methylpropane-1-one.

3. A quick-drying corrosion-resistant topcoat according to claim 1, characterized in that: The preparation method of the anticorrosive resin comprises the following steps: S1: placing hydroxychloroacetic acid resin and 2-chloroacrylic acid in toluene, stirring and mixing, adding p-toluenesulfonic acid, heating to react, and collecting the product after reduced pressure distillation to obtain a modified chloroacetic acid resin; S2: Place the modified chloroacetic acid resin and 2-amino-5-fluorotrifluorotoluene in N,N-dimethylformamide, add a catalyst, heat to 55-65°C and react for 6-8h, collect the product after reduced pressure distillation, and obtain an anti-corrosion resin.

4. A quick-drying corrosion-resistant topcoat according to claim 3, characterized in that: In step S1, the temperature of the temperature-raising reaction is 90-95° C. and the time is 3-5 hours.

5. The quick-drying corrosion-resistant topcoat according to claim 3, characterized in that: In step S2, the catalyst is potassium carbonate.

6. The quick-drying corrosion-resistant topcoat according to claim 1, characterized in that: The preparation method of the mercaptolated dickite comprises the following steps: SS1: Place dickite in deionized water, ultrasonically disperse for 10-15 minutes, add (3-carboxypropyl)trimethylammonium chloride, stir thoroughly for 8-10 hours, filter, wash and dry to obtain modified dickite; SS2: Place the modified dickite in anhydrous ethanol, ultrasonically disperse it for 12-15 minutes, add mercaptoethylamine and a composite catalyst, heat to 60-65°C and react for 5-6 hours, filter, wash and dry to obtain the mercapto dickite.

7. A quick-drying corrosion-resistant topcoat according to claim 6, characterized in that: In step SS2, the composite catalyst is 4-dimethylaminopyridine and dicyclohexylcarbodiimide in a ratio of 0.3-1:0.9-3.

8. A process for preparing the quick-drying corrosion-resistant topcoat as claimed in claim 1, characterized in that: The following steps are involved: Step 1, epoxy acrylate resin, anti-corrosion resin, mercapto-modified dickite, defoamer, antioxidant, emulsifier and leveling agent are mixed uniformly to obtain component A; Step 2: Evenly mix the photoinitiator and deionized water to obtain component B.

Citation Information

Patent Citations

  • A heat-resistant and corrosion-resistant epoxy paint and its preparation method

    CN106280867B

  • Preparation method for molybdenum disulfide nanosheet with reactive group-containing surface

    CN103833081A

  • Composite coating for spraying machines

    CN104817860A

  • Inorganic anti-corrosive paint for underground sewage concrete pipeline, and preparation method of inorganic anti-corrosive paint

    CN105601326A

  • Method for preparing ultrathin dickite by intercalating potassium acetate in splinters

    CN105883839A